2015
DOI: 10.1158/1078-0432.ccr-15-0578
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage Cancer Patients Remain Highly Responsive to Immune Activation by the Selective TLR8 Agonist Motolimod (VTX-2337)

Abstract: Purpose: Immunotherapy as a treatment for cancer holds the promise of complete and durable tumor remission, yet the immunosuppressive environment created by many tumors, advanced patient age, and previous treatments with cytotoxic agents may limit the approach. The activity of motolimod (VTX-2337), a potent and selective Toll-like receptor 8 (TLR8) agonist, was therefore assessed in the context of advanced, late-stage cancer patients. Experimental Design: The repertoire of mediators induced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…In vivo analytes were quantified in plasma samples collected from patients before and 8 h following motolimod dosing. Post-dose levels of responsive mediators in patients treated with motolimod plus PLD showed statistically significant increases consistent with previous findings in human volunteers and cancer patients who received motolimod monotherapy [18, 19] and ovarian cancer patients treated with motolimod plus PLD [20] (Figure 2A and B; supplementary Table S3, available at Annals of Oncology online). In vivo responses were not significantly associated with longer OS or irPFS (data not shown).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In vivo analytes were quantified in plasma samples collected from patients before and 8 h following motolimod dosing. Post-dose levels of responsive mediators in patients treated with motolimod plus PLD showed statistically significant increases consistent with previous findings in human volunteers and cancer patients who received motolimod monotherapy [18, 19] and ovarian cancer patients treated with motolimod plus PLD [20] (Figure 2A and B; supplementary Table S3, available at Annals of Oncology online). In vivo responses were not significantly associated with longer OS or irPFS (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…TLR8 is localized in endosomal compartments of monocytes and mDC and its activation stimulates the release of inflammatory mediators, including T cell helper 1 (Th1)-polarizing cytokines [18, 19]. Motolimod (previously identified as VTX-2337) is a synthetic, small molecule, selective agonist of TLR8 comprising a 2-aminobenzazepine core [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Doses that were proven to be safe and biologically active for each species were used (10, 17). A dose-dependent increase in cytokines and chemokines indicative of TLR8-induced monocyte activation— including IL-6, MCP-1, and MIP-1β—were observed in all species (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Five men and 5 women healthy volunteers enrolled in a randomized, open-label, phase 1 study of motolimod (Study VRXP-A105) received two doses of motolimod 2.5 mg/m 2 SC separated by one week (17). Plasma samples were collected pre-dose and 6 hours after dosing, and analyzed for mediator levels as described above.…”
Section: Methodsmentioning
confidence: 99%
“…VTX-2337 is a synthetic TLR8 agonist that demonstrated effectiveness in preclinical models of head and neck cancer through innate immune modulation (Stephenson, et al, 2013). Subsequent phase I dose escalation studies demonstrated safety in patients with advanced cancer (Dietsch, et al, 2015;Northfelt, et al, 2014). However, clinical benefit of this strategy is currently unproven and concerns regarding off-target effects persist.…”
Section: Modulators Of Innate Immunitymentioning
confidence: 99%